Prevalence and age-of-onset distributions of DSM IV mental disorders and their severity among school going Omani adolescents and youths: WMH-CIDI findings - Morsi Magdi; Al-Kharusi Hilal; Al-Adawi Samir; Jaju Sanjay; Al-Riyami Asya (BMC, 2009)
Abstract Background There is a dearth of studies exploring the magnitude of mental disorders amongst adolescents and youths in the Arab world. To our knowledge, this phase 2 survey in Oman is the first nationally representative school-based study to determine the prevalence of DSM-IV mental disorders (lifetime and over the preceding 12 months), their age-of-onset distributions and determine their severity over the past 12 months using the World Mental Health-Composite International Diagnostic Interview, the WMH-CIDI, used for international comparison. Methods A total of 1,682 (91.61%) students out of 1836 students who formed the phase 2 random sub-sample of a multi-stage, stratified, random sampling design (phase 1), participated in the face-to-face structured interview using the Arabic-version of WMH-CIDI 3.0. Results The phase 1 results using the General Health Questionnaire (GHQ-12) and Child Depression Inventory (CDI) showed depressive symptoms to be 17% prevalent in the larger sample of 5409 adolescents and youths. Amongst the phase 2 respondents from this sample, 13.9% had at least one DSM IV diagnostic label. The lifetime prevalence of Major Depressive Disorder (MDD) was 3.0%; Bipolar Mood Disorder (BMD) was 1%, Specific phobia 5.8% and Social phobia 1.6%. The female gender was a strong predictor of a lifetime risk of MDD (OR 3.3, 95% CI 1.7-6.3, p = 0.000); Any Mood Disorders (OR 2.5, 95% CI 1.4-4.3, p = 0.002) and Specific Phobia (OR 1.5, 95% CI 1.0-2.4, p = 0.047). The severity of illness for cases diagnosed with 12 month DSM IV disorders was found to be 80% lower in females (OR 0.2, 95%CI 0.0-0.8). The estimates over the previous 12 month period when compared with the lifetime prevalence showed a 25% to 40% lower prevalence for MDD, Specific phobia, Social phobia, Any Anxiety Disorders (AAD) and Any Mood disorders (AMD) while the rate was 80% lower for Separation Anxiety Disorder/Adult Separation Anxiety (SAD/ASA). Mood disorders were significantly lower in the 14-16 age groups (70% lower) in comparison to the older age groups and AMD showed a linear increase in prevalence across increasing age groups (p = 0.035). Conclusion The implications of the present findings are not clear cut, however this study endorses the adult CIDI studies findings that mental disorders do begin earlier in life. The relatively lower prevalence of DSM IV depressive disorders cautions against any conclusive interpretation of the inflated results based on the exclusive study of the depressive symptoms alone in the same sample in the same time period. The female gender proved to be a strong predictor of lifetime risk of MDD, any mood disorder and specific phobia. Under-reporting by males or some other gender-specific factors may have contributed to such a discrepancy. The odds of the severity of illness for cases with 12 month DSM IV disorders were significantly lower in females.